Effects of tidal cycle on greenhouse gases emissions from a tropical estuary. (April 2023) - Khan, Mohammad Atif; Kumar, Sanjeev; Roy, Rajdeep; Prakash, Satya; Lotliker, Aneesh A.; Baliarsingh, Sanjiba Kumar
Abstract: The potential effects of tidal and diel cycles on fluxes and concentrations of carbon dioxide (pCO2 ), methane (CH4 ), and nitrous oxide (N2 O) along with associated biogeochemical processes remain poorly understood in tropical estuaries. The present study, based on six-hourly sampling for nine consecutive days at three locations along the salinity gradient in the Mahanadi estuary of India, revealed that the tidal forcing affected pCO2 and CH4 in the mixing zone with elevated concentrations during low tide with maximum concentrations up to 21, 606 μatm and 285 μM, respectively. pCO2 increased with decrease in tidal height within low and high tide duration as well, possibly due to higher relative contribution of freshwater with high CO2 . N2 O, on the other hand, showed no significant variability with tidal cycle or water level fluctuation during high and low tide. Barring the offshore region, the study area was source of greenhouse gases to the atmosphere. Highlights: Tidal cycle and fluxes of greenhouse gases in the estuary were coupled. CO2 and CH4 fluxes were high during low tide. N2 O distribution did not change significantly with tide. Largely, the estuary was source for greenhouse gases to the atmosphere.